2017
DOI: 10.3390/pathogens6040049
|View full text |Cite
|
Sign up to set email alerts
|

Zika Virus Persistently and Productively Infects Primary Adult Sensory Neurons In Vitro

Abstract: Zika virus (ZIKV) has recently surged in human populations, causing an increase in congenital and Guillain-Barré syndromes. While sexual transmission and presence of ZIKV in urine, semen, vaginal secretions, and saliva have been established, the origin of persistent virus shedding into biological secretions is not clear. Using a primary adult murine neuronal culture model, we have determined that ZIKV persistently and productively infects sensory neurons of the trigeminal and dorsal root ganglia, which innerva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 46 publications
3
15
1
1
Order By: Relevance
“…Furthermore, the inability of ZIKV disturb the BBB permeability, after early life infection, reinforces the possibility of viral accesses CNS by peripheral neurons. This is also supported by the detection of ZIKV negative strain in the DRG of neonates (6 dpi), and corroborates with previous studies that demonstrated ZIKV replication in explants and neurons from DRG of ZIKV-infected mice (16, 50). In addition, it was previously demonstrated that ZIKV reaches CNS without disrupt BBB by transcytosis, interfering on its permeability only at late stages of infection (15).…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, the inability of ZIKV disturb the BBB permeability, after early life infection, reinforces the possibility of viral accesses CNS by peripheral neurons. This is also supported by the detection of ZIKV negative strain in the DRG of neonates (6 dpi), and corroborates with previous studies that demonstrated ZIKV replication in explants and neurons from DRG of ZIKV-infected mice (16, 50). In addition, it was previously demonstrated that ZIKV reaches CNS without disrupt BBB by transcytosis, interfering on its permeability only at late stages of infection (15).…”
Section: Discussionsupporting
confidence: 91%
“…It has been shown that ZIKV persistently infects various trigeminal and dorsal root sensory neurons. Conversely, autonomic sympathetic and parasympathetic neurons were shown to be non-permissive to infection [152]. This is supported by the finding that cells of the peripheral nervous system are much less susceptible to infection than cells of the central nervous system (CNS), with all major CNS cell types being susceptible to infection, particularly oligodendrocytes [153].…”
Section: Infection Of Foetal Cellsmentioning
confidence: 96%
“…Вполне вероятно, что при использовании более высоких доз (10 7 -10 8 ТЦД 50 ) будет достигаться более эффективная репликация вируса в клетках опухоли, что в итоге может привести к лизису клеток глиобластомы и полной регрессии всех привитых ксенографтов глиобластомы. Известно, что вирус Зика способен длительно персистировать в инфицированном организме, в том числе и в клетках нервной системы (Swartwout et al, 2017) Titer, TCID 50 /mL 2 · 10 5 (8 · 10 4 -5 · 10 5 ) * 5 · 10 5 (2 · 10 5 -1.2 · 10 6 ) 2 · 10 5 (7 · 10 4 -6.5 · 10 5 ) 10 3 (6 · 10 2 -2.5 · 10 3 ) (Mazar et al, 2018). В этой работе приведены данные, свидетель ствующие о рецепторном взаимодействии вируса Зика с клеточным поверхностным гликопротеином CD24, и экспериментально доказана зависимость инфекционности вируса Зика для клеток от уровня презентации CD24 на клеточной поверхности.…”
Section: результаты и обсуждениеunclassified